Electrophore membrane
Patent Information
- Application Number
- JP2022556051
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-18
- Filing Date
- 2021-03-16
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-03-16
Smart Images

Figure 0007637694000001 
Figure 0007637694000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a sol composition for producing a dielectric coating, in particular on a metal substrate. The present invention also relates to said dielectric coating, its use for producing an electronic device, an optoelectronic device, in particular a solar cell. The present invention also relates to a method thereof. [Background technology]
[0002] Solar cells are usually constructed of several layers including a substrate, a back electrode, an absorber layer containing a pn junction, and a front electrode.
[0003] If the substrate is metallic, it is often necessary to coat it with a dielectric layer to insulate the solar cell from the conductive substrate. This dielectric layer must be able to withstand 250V without arcing. It must also be able to withstand the thermal cycling that occurs during solar cell fabrication, typically annealing at 550°C to form the CIGS layer, without delaminating or changing properties.
[0004] Furthermore, since the layers applied onto the dielectric layer are very thin (on the order of 1 micron), they can only be continuous if the dielectric layer is very smooth. As a result, the roughness (Rz) of the dielectric layer must be significantly lower than 1 μm.
[0005] Current solutions that meet conventional requirements and have adequate roughness have distorted networks that lead to cracking of the dielectric layer. Reducing the internal stresses has been done to the extent that it compromises roughness. Summary of the Invention [Problem to be solved by the invention]
[0006] Therefore, there is a need for a dielectric coating that has a good compromise between roughness, internal stress and thermal stability. [Means for solving the problem]
[0007] To this end, a first subject of the invention consists of a sol composition for producing a dielectric layer on a metal substrate, comprising: - 10 to 30% by weight of the sol composition of a precursor comprising a trialkoxysilane, - 10-40% by weight of the sol composition of titanium dioxide particles having a median diameter of less than 500 nm; - 4.5 to 36% by weight of the sol composition of silica particles having a particle size distribution D90 of less than 100 nm; - 5 to 15% by weight of the sol composition of a solvent capable of making said precursor miscible in water, - 0.1 to 2% by weight of the sol composition of an acid catalyst; The remainder is water.
[0008] The sol composition according to the invention may comprise: - 10 to 30% by weight of the sol composition of a precursor comprising a trialkoxysilane, - 10-40% by weight of the sol composition of titanium dioxide particles having a median diameter of less than 500 nm; - an aqueous dispersion of silica in an amount of 30 to 60% by weight of a sol composition, the aqueous dispersion comprising 15 to 60% by weight of silica particles having a particle size distribution D90 of less than 100 nm; - 5 to 15% by weight of the sol composition of a solvent capable of making said precursor miscible in water, - 0.1 to 2% by weight of the sol composition of an acid catalyst.
[0009] The sol composition according to the invention may also have any of the features listed below, considered individually or in combination. - trialkoxysilanes are organofunctional trialkoxysilanes of general formula R'-Si(OR)3, where R' is an organofunctional group and R represents an alkyl; - trialkoxysilane is an alkyltrialkoxysilane, the trialkoxysilane is selected from methyltrialkoxysilane, ethyltrialkoxysilane and propyltrialkoxysilane; - trialkoxysilane is methyltrimethoxysilane, - the precursor is a mixture of at least one tetraalkoxysilane and at least one trialkoxysilane; the content of the precursor is comprised between 15 and 25% by weight of the sol composition; the solvent is selected from alcohols, ketones and mixtures thereof; - The solvent is acetone, - The diameter of titanium dioxide particles is between 200 and 1000 nm; - The titanium dioxide particles are coated with alumina in an amount of 2-6% by weight of the TiO2 particles; the content of the aqueous dispersion of silica is comprised between 35 and 55% by weight of the sol composition, the aqueous dispersion of silica comprises 40 to 55% by weight of the aqueous dispersion; - the aqueous dispersion of silica comprises a mixture of silica particles of two different size ranges, the first range being between 50 and 120 nm and the second range being between 3 and 25 nm; - The acid catalyst includes phosphoric acid.
[0010] A second subject of the invention consists of a metal substrate coated, on at least a portion of at least one of its surfaces, with a dielectric layer of at least 10 μm comprising: - 20-70% by weight of titanium dioxide particles having a median diameter of less than 500 nm in the dielectric layer; - 20-70% by weight of silica particles having a particle size distribution D90 of less than 100 nm in the dielectric layer; - 5-18% by weight of a polymerized trialkoxysilane precursor of the dielectric layer; - 0.1-2% acid catalyst in the dielectric layer.
[0011] A third subject of the invention consists of a method for producing a sol composition, comprising the following steps: - providing o 10 to 30 parts by weight of a precursor comprising a trialkoxysilane, o 10 to 40 parts by weight of titanium dioxide particles having a median diameter of less than 500 nm; o an aqueous dispersion of silica from 30 to 60 parts by weight, the aqueous dispersion comprising 15 to 60% by weight of silica particles having a particle size distribution D90 of less than 100 nm, o 5 to 15 parts by weight of a solvent capable of making the precursor miscible in water, 0.1 to 2 parts by weight of an acid catalyst, - mixing said ingredients.
[0012] A fourth subject of the invention consists of a sol-gel process for producing a dielectric layer on a metallic substrate, comprising the following steps: (i) providing a metal substrate and a sol composition comprising: o 10-30% by weight of the sol composition of a precursor comprising a trialkoxysilane; o 10-40% by weight of the sol composition of titanium dioxide particles having a median diameter of less than 500 nm; o an aqueous dispersion of silica at 30-60% by weight of the sol composition, the aqueous dispersion comprising 15-60% by weight of silica particles having a particle size distribution D90 of less than 100 nm; o 5-15% by weight of the sol composition of a solvent capable of making the precursor miscible in water; 0.1 to 2% by weight of the sol composition of an acid catalyst; - (ii) depositing the sol composition onto at least one surface of a metal substrate; - (iii) evaporating the solvent to form a dielectric layer.
[0013] The sol-gel process according to the invention may also have any of the features listed below, considered individually or in combination. - depositing a sol composition of at least 20 μm; - step (iii) comprises a drying step in which the peak metal temperature of the metal substrate is comprised between 120 and 200 °C and the drying time is comprised between 30 seconds and 4 minutes, the method further comprises a step (iv) of annealing the dielectric layer at a peak metal temperature of the metal substrate comprised between 300 and 600° C. for a period of between 30 seconds and 4 minutes.
[0014] A fifth subject of the invention consists of a method for producing a solar cell, comprising: (i) providing a metal substrate coated on at least a portion of at least one of its surfaces with a dielectric layer of at least 10 μm comprising: o 20-70% by weight of titanium dioxide particles having a median diameter of less than 500 nm in the dielectric layer; o 20-70% by weight of silica particles having a particle size distribution D90 of less than 100 nm in the dielectric layer; o 5-18% by weight of a polymerized trialkoxysilane precursor of the dielectric layer; o 0.1-2% acid catalyst in the dielectric layer; - (ii) depositing a molybdenum-based back electrode onto the dielectric layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The invention will be better understood on reading the following description, which is provided purely for illustrative purposes and is not intended to be limiting in any way.
[0016] It should be noted that, as used herein, the terms "over" and "on" are both inclusive of "directly on" (with no intermediate materials, elements, or spaces disposed therebetween) and "indirectly on" (with intermediate materials, elements, or spaces disposed therebetween). For example, forming an element "on" a substrate can include forming the element directly on the substrate with no intermediate materials / elements disposed therebetween, and forming the element indirectly on the substrate with one or more intermediate materials / elements disposed therebetween.
[0017] By metal substrate is meant an element having a flat shape, i.e. its thickness is thin compared to its other dimensions. Generally speaking, its thickness is 500 to 4000 times smaller than its width. The substrate may be made of a single material or a composite assembly. Carbon steel, stainless steel, aluminum, copper and zinc may be cited as non-limiting examples of metallic materials. Carbon steel and stainless steel are preferred. The metal substrate may be in the form of a coil or a sheet.
[0018] The dielectric coating of the present invention is obtained by a sol composition. The sol-gel method is a method for producing solid materials from small molecules. This method is used to prepare metal oxides, especially oxides of silicon (Si) and titanium (Ti). In this method, monomers are converted into a colloidal solution (sol), which acts as a precursor for individual particles or an integrated network (or gel) of reticulated polymers. Typical precursors are metal alkoxides.
[0019] The sol composition according to the present invention first includes a precursor comprising a trialkoxysilane, preferably a non-hydrogenated trialkoxysilane.
[0020] The precursor may be an organofunctional trialkoxysilane of general formula R'-Si(OR)3, where R' represents an organofunctional group and R represents an alkyl.
[0021] The organofunctional trialkoxysilanes may in particular be chosen from methyltrimethoxysilane, methyltriethoxysilane, methyltripoxysilane, methyltributoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltripoxysilane, ethyltributoxysilane, propyltrimethoxysilane, propyltriethoxysilane, propyltripoxysilane, propyltributoxysilane, (3-glycidyloxypropyl)trimethoxysilane, (dibutyl-oxyaluminoxy)triethoxysilane, 3-aminopropyltriethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-mercaptopropyltriethoxysilane, aminophenyltriethoxysilane, tridecafluoro1,1,2,2-tetrahydrooctyltriethoxysilane, chloropropyltriethoxysilane, amyltriethoxysilane, vinyltriethoxysilane or phenyltriethoxysilane or mixtures thereof.
[0022] The trialkoxysilane is preferably an alkyltrialkoxysilane, more preferably selected from methyltrialkoxysilane, ethyltrialkoxysilane or propyltrialkoxysilane. More preferably, the trialkoxysilane is selected from methyltrimethoxysilane, methyltriethoxysilane, methyltrippropoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltrippropoxysilane, propyltrimethoxysilane, propyltriethoxysilane or propyltrippropoxysilane. These trialkoxysilanes further improve the thermal resistance of the dielectric film.
[0023] Due to the trialkoxy functionality, the network obtained in the precursor is preferably a trivalent network interspersed with organic functional groups. It has less distortion and limited cracking than a silica network. The flexibility of this network can be tailored by the choice of organic functional groups.
[0024] The influence of these groups is such that the precursor can also be a mixture of at least one tetraalkoxysilane and at least one trialkoxysilane. In particular, it can be a combination of tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane or tetrabutoxysilane with methyltrimethoxysilane, methyltriethoxysilane, methyltripropoxysilane, methyltributoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltrippropoxysilane or ethyltributoxysilane. In that case, the tetrahedral network of the first precursor is balanced by the trivalent network of the second precursor, which limits the stress in the network.
[0025] The precursor is specifically methyltrimethoxysilane (MTMOS), an organosilicon compound with the base CH3Si(OCH3)3. Films formed from this precursor are highly resistant to temperature. Under inert gas, the precursor slowly begins to decompose at around 500-600°C.
[0026] Methyltrimethoxysilane is easily hydrolyzed and its condensation can be easily controlled under acidic conditions, so that its shelf life is at least 24 hours, which allows some latitude in the method of producing the dielectric coating.
[0027] The polymerization process of this precursor is as follows. CH3Si(OCH3)3+H2O→OH-Si(CH3)(OCH3)2+CH3-OH (OCH3)2(CH3)Si-OH+OH-Si(CH3)(OCH3)2→[(OCH3)2(CH3)Si-O-Si(CH3)(OCH3)2]+HOH or (OCH3)2(CH3)Si-OCH3+OH-Si(CH3)(OCH3)2→[(OCH3)2(CH3)Si-O-Si(CH3)(OCH3)2]+CH3-OH
[0028] Thus, polymerization is associated with the formation of a three-dimensional network of siloxane [Si-O-Si] bonds accompanied by the generation of HOH and ROH species.
[0029] The content of precursor is comprised between 10 and 30% by weight of the sol composition. Below 10% by weight, it has been observed that the content is not sufficient to obtain good cohesion of the coating. Above 30% by weight, microcracks tend to appear, which affect the electrical insulation. Preferably, the content of precursor is comprised between 15 and 25% by weight, which gives the best compromise between internal stress and thermal stability.
[0030] In the sol composition, the precursor may be in hydrolyzed form. The content ranges given in the specification do not take this hydrolysis into account. In particular, the precursor content ranges are the content ranges of unhydrolyzed precursor. For a given sol composition, the content range of hydrolyzed precursor can be easily calculated.
[0031] The sol composition further comprises a solvent capable of rendering the precursor miscible in water so that the hydrolysis that occurs is homogeneous.
[0032] The solvent can be chosen among alcohols, ketones and mixtures thereof. The alcohols are preferably chosen among the monohydric alcohols that represent the best compromise between water solubility and boiling point. Possible monohydric alcohols are ethanol, butanol, isopropanol, methoxypropanol and mixtures thereof. The ketones are preferably chosen among acetone and methyl ethyl ketone. Acetone is preferred, as it is 100% miscible with water, as this is advantageous for the dispersion of the particles. Acetone also evaporates at low temperatures (56° C.), but not too low so that it does not evaporate in the spray mist when the sol composition is sprayed on the substrate.
[0033] A mixture of solvents can be used to favor the wetting of the sol composition on the metal substrate and provide better evaporation control.
[0034] The content of the solvent(s) is comprised between 5 and 50% by weight of the sol composition. Below 5% by weight the composition is too viscous. Above 50% by weight, dilution is paramount and thick layers with good electrical insulation cannot be obtained. Preferably, the content of the solvent is comprised between 5 and 15% by weight, which represents the best compromise between viscosity and dilution.
[0035] The sol composition further comprises titanium dioxide particles having a median diameter of less than 500 nm, the content being 10-40% by weight of the sol composition. TiO2 is very stable, resistant to high temperatures and easily disperses in water. Preferably, the content of titanium dioxide particles is comprised between 20-30% by weight.
[0036] The median particle size prevents larger particles from protruding from the surface of the dielectric coating and keeps the roughness at a low level. More preferably, the particle size is comprised between 200 nm and 1000 nm.
[0037] Preferably, the surface of the TiO2 particles is coated to stop the TiO2 from being photoactive, which may otherwise degrade the dielectric coating and the corresponding solar cell in the long term. The surface coating can be alumina or silica. Alumina is preferred as it is believed to help the dielectric layer maintain its integrity during thermal expansion. When the TiO2 is coated with alumina, it typically contains 2-6% alumina by weight of the alumina-coated TiO2 particles.
[0038] The TiO2 particles are preferably not surface functionalized with hydroxyl groups, hydrogen polysiloxanes, or dihydrogen polysiloxanes.
[0039] Since TiO2 by itself is not able to provide sufficient cohesion to the dielectric coating, the sol composition further comprises 4.5-36% by weight of the sol composition of silica particles having a particle size distribution D90 of less than 100 nm. Silica is also an electrical insulator, chemically inert, and resistant to high temperatures.
[0040] The sol composition is preferably Sol CompositionThe silica particles are contained in an amount of 14 to 30% by weight.
[0041] Since the silica particles are significantly smaller and less dense than the TiO2 particles, the surface of the dielectric coating is mainly composed of silica, which reduces the roughness of the coating. The silica particles preferably have a diameter comprised between 3 and 120 nm.
[0042] The silica particles are preferably not surface functionalized with hydroxyl groups, hydrogen polysiloxanes or dihydrogen polysiloxanes.
[0043] Optionally, the sol composition comprises a mixture of silica particles of two different size ranges, a first range of 50-120 nm and a second range of 3-25 nm. In that case, the particles of the second size distribution can represent up to 30% by weight of the total weight of silica particles, preferably between 10-30% by weight. This further improves the roughness of the dielectric coating.
[0044] According to a preferred embodiment, silica is added to the sol composition in the form of an aqueous dispersion of silica. In that case, 4.5-36% by weight of silica particles of the sol composition corresponds to an aqueous dispersion of silica of 30-60% by weight of the sol composition, with 15-60% by weight of silica particles of the aqueous dispersion, together with water added as the remainder of the sol composition. The aqueous dispersion of silica is a source of pure silica that is an electrical insulator, chemically inert and resistant to high temperatures. It is also a source of water for the hydrolysis of the sol-gel precursor.
[0045] The sol composition preferably contains an aqueous dispersion of silica in an amount of 35-55% by weight of the sol composition, and the aqueous dispersion of silica contains silica particles in an amount of 40-55% by weight of the aqueous dispersion. This concentration allows the gel obtained by polymerization of the sol composition to dry more easily, and the dielectric coating also dries, preventing cracking. Thanks to the presence of water in this proportion, the hydrolysis of the precursor takes place under favorable conditions.
[0046] According to one variant, before mixing the components of the sol composition, the pH of the aqueous dispersion of silica is maintained between 9 and 10 to limit the generation of silicates. The pH can be controlled by the addition of a solution of a base, such as sodium hydroxide, sodium oxide, ammonium hydroxide or ammonium oxide.
[0047] According to another variant, the silica is dispersed in deionized water at a pH comprised between 4 and 5.
[0048] The sol composition further comprises an acid catalyst between 0.1-2% by weight of the sol composition, preferably 0.2-0.8%. Its acidic nature allows a dense coating to be obtained. This catalyst also controls the polymerization rate. Thus, the catalyst is selected based on the rate required depending on the application method. If a faster polymerization rate is preferred, strong acids such as hydrochloric acid or sulfuric acid are considered. If the shelf life of the sol composition must be extended to 1-2 days so that the composition is prepared before application and can be stored during that time, weak acids are preferred. The weak acids can be selected from phosphoric acid, phosphorous acid, formic acid, acetic acid, lactic acid, oxalic acid, citric acid, tartaric acid, and benzoic acid. Inorganic acids are preferred for their thermal stability so that the coating network is not contaminated with carbon residues. Phosphoric acid is particularly preferred as its trivalent nature makes it very rigid.
[0049] The sol composition further comprises water as a remainder. By the expression "the remainder is water" it is meant that water remains in the sol composition even after the hydrolysis of the precursor. Due to the presence of water, the hydrolysis of the precursor takes place under good conditions, the silica and TiO2 particles are well stabilized and dispersed, and the evaporation of the solvent is better controlled. The water is preferably deionized water.
[0050] If the silica is added in the form of an aqueous dispersion, it is preferred to provide water only through the aqueous dispersion.
[0051] This sol composition produces extremely low roughness (R a is less than 100 nm, R zDielectric layers thicker than 20 μm (with thicknesses between 200 and 600 nanometers) can be obtained without pinholes. These layers can be heated up to 600 °C for several hours without cracking during heating and cooling. Furthermore, these layers are efficient barriers to the diffusion of iron from the steel substrate, which eliminates the need for a barrier layer between the steel substrate and the PV cell.
[0052] The sol composition is prepared by mixing all the different components together.
[0053] Alternatively, the sol composition is a two-component product. In that case, the first component is preferably prepared by mixing titanium dioxide particles, an aqueous dispersion of silica, and a solvent. The second component is preferably prepared by mixing a precursor and an acid catalyst. These two components are then mixed together before using the sol composition.
[0054] Optionally, the sol composition is finally filtered through 1 μm to remove possible agglomerates.
[0055] With respect to the method, once the metal substrate and the sol composition are provided, the composition is deposited onto at least a portion of at least one surface of the substrate. This can be done, for example, by dip coating, spin coating, roll coating, slot die coating, spraying, inkjet printing. A slot die is preferred due to the surface uniformity it provides.
[0056] It is preferred that the sol composition be applied in an amount sufficient to obtain a dry dielectric layer at least 10 μm thick, below which the coating may not be sufficiently dielectric. The applied wet sol composition is at least 20 μm thick.
[0057] In the next step, the sol gradually progresses towards the formation of a gel-like network containing both liquid and solid phases. The simplest method is to allow precipitation and evaporation of the solvent, resulting in a dielectric layer. Preferably, evaporation of water also occurs. A drying step is preferably performed to rapidly dry the applied film to obtain a dielectric layer. Drying can be performed by convection, induction, infrared or other suitable method, in an oven, in a continuous or batch manner. More preferably, the peak metal temperature of the metal substrate covered with the film is comprised between 120 and 200° C. and the drying time is comprised between 30 seconds and 4 minutes.
[0058] Optionally, for optimal dielectric performance, the dielectric layer is further annealed under inert gas to completely remove any water trapped within the coating from the layer. Such annealing prevents water from degassing and thus degrading subsequent layers in subsequent steps of the solar cell manufacturing process. Annealing can be performed in an oven, in a continuous or batch manner, by convection, induction or any other suitable method. More preferably, the peak metal temperature of the metal substrate covered with the dielectric layer is comprised between 300 and 600°C, more preferably between 500 and 600°C, even more preferably between 540 and 560°C, and the drying time is comprised between 30 seconds and 4 minutes.
[0059] The sol-gel coating comprises 20-70% by weight of silica particles, 20-70% by weight of titanium dioxide particles, and the remaining part of the coating comprises polymerized precursors, i.e., a three-dimensional network of siloxane (Si-O-Si) bonds, the network preferably comprising Si atoms bonded to organic functional groups, and an acid catalyst. In particular, the sol-gel coating comprises 5-18% of the network of the dielectric layer and 0.1-2% of the acid catalyst of the dielectric layer. The sum of the contents of each element is equal to 100%.
[0060] The sol-gel coatings were characterized by SEM (particle size and nature), X-ray fluorescence (Si and Ti content) and IR spectroscopy (SiO2 and network content).
[0061] The resulting sol-gel coating is at least 10 μm thick to have good dielectric properties. The sol-gel coating has a roughness R of less than 100 nm. a and roughness R less than 600 nm z The sol-gel coating has an adhesion to a metal substrate of at least 3 as measured by a tape test according to ASTM D3359. Its electrical insulation is such that the resistance measured with a gigahometer between the metal substrate and a drop of saturated salt water deposited on the surface of the sol-gel coating is at least 272 gigaohms under 250V for at least 3 minutes. Its breakdown voltage is at least 1000V.
[0062] Once the sol composition has been coated on a substrate, dried and optionally heat treated, the different layers that make up the solar cell can be deposited.
[0063] According to one variant of the invention, the solar cell is a CIGS solar cell. CIGS refers here to a family of materials that have desirable properties for use as an absorber layer in thin-film solar cells. Copper indium diselenide (CuInSe2 or CIS) and its higher bandgap variants copper indium gallium diselenide (Cu(In / Ga)Se2 or CIGS), copper indium aluminum diselenide (Cu(In / Al)Se2), copper indium gallium aluminum diselenide (Cu(In / Ga / Al)Se2) and all of these compounds in which sulfur replaces part of the selenium are members of this family.
[0064] CIGS thin-film solar cells are usually manufactured by first depositing a molybdenum-based back electrode on a substrate such as glass, stainless steel foil, carbon steel foil, or other functional substrate. It can be done by RF or DC magnetron sputtering. The molybdenum-based back electrode can be made of a layer of molybdenum (Mo), a layer of molybdenum-sodium (Mo / Na), or a layer of molybdenum-potassium (Mo / K), or it can be made of multiple sublayers of Mo and / or Mo / Na and / or Mo / K. Alternatively, a zirconium nitride barrier layer can be added on top of the back electrode to block diffusion, so that molybdenum can be replaced by other metals such as silver, aluminum, copper, etc.
[0065] A relatively thick layer of CIGS is then deposited on the molybdenum layer by known techniques. In the precursor technique, the metals (Cu / In / Ga) are first deposited on the substrate using physical vapor deposition (PVD) techniques (evaporation or sputtering), chemical baths, or electroplating. A selenium-bearing gas is then reacted with the metal layer in a diffusion furnace at temperatures ranging up to about 600° C. to form the final CIGS composition. The most commonly used selenium-bearing gas is hydrogen selenide, which is highly toxic to humans and requires extreme caution in its use. A second technique avoids the use of hydrogen selenide gas by co-evaporating all of the CIGS components onto the hot substrate from separate thermal evaporation sources. In a third technique, the CIGS layer is deposited by DC magnetron sputtering using planar and / or rotating magnetrons.
[0066] The CIGS layer can be made of multiple sublayers. In certain embodiments, each sublayer has the same composition. In other embodiments, the composition of the sublayers differs such that the CIGS layer has a composition that grades in at least one elemental concentration from at least one sublayer to another sublayer. In some embodiments, each sublayer has the same thickness, while in other embodiments, at least two sublayers have different thicknesses.
[0067] The n-type material most often used with CIGS absorbers to form a thin "window" or "buffer" layer is cadmium sulfide (CdS). It is much thinner than the CIGS layer and can be applied by chemical bath deposition (CBD) or DC sputtering. Due to the toxicity and waste disposal issues associated with cadmium, ZnS can be used as an alternative. It can be made by AC reactive sputtering from an elemental zinc target and injection of hydrogen sulfide.
[0068] Finally, the window or buffer layer is covered with a relatively thick transparent conductive oxide that is also an n-type semiconductor. Traditionally, zinc oxide (ZnO) has been used as an alternative to the traditional, but more expensive, indium tin oxide (ITO). In recent years, aluminum doped ZnO (AZO) has been shown to perform almost as well as ITO and has become the material of choice in the industry. It can be prepared by magnetron sputtering.
[0069] Optionally, additional conductive layers, such as a top metallization layer or a passivation layer, may be deposited over the buffer layer. Patterning and interconnection steps may also be performed to provide a monolithically integrated device.
[0070] Alternatively, the dielectric films obtained from the sol compositions may be used in the manufacture of other electronic or optoelectronic devices, such as phototransistors, photomultiplier tubes, light emitting diodes (LEDs), and the like. EXAMPLES
[0071] A first sol composition was prepared by mixing the following: On the one hand, 40 g of titanium dioxide particles coated with 4% by weight of alumina (Ti-Pure® R900 supplied by Chemours® (DuPont®) with a median particle size of 410 nm), 70 g of an aqueous dispersion of silica containing 50% by weight of silica with a particle size distribution D90 of less than 100 nm (Levasil CT3PL supplied by Nouryon®) and 15 g of acetone. on the other hand, 30 g of trimethoxymethylsilane and 0.5 mL of phosphoric acid as an 85% aqueous solution.
[0072] These two components were then mixed together.
[0073] A second sol composition was prepared by mixing the following: on the one hand, 40 g of titanium dioxide particles coated with 4% by weight of alumina (Ti-Pure® R900 supplied by Chemours® (DuPont®) with a median particle size of 410 nm), 60 g of an aqueous dispersion of silica (Levasil CT3PL supplied by Nouryon®) containing 50% by weight of silica with a particle size distribution D90 of less than 100 nm and 25 g of technical ethanol, on the other hand, 30 g of trimethoxymethylsilane and 0.5 mL of phosphoric acid as an 85% aqueous solution.
[0074] The two components were then mixed with 25 g of an aqueous dispersion of silica (Ludox® TM-50 supplied by Sigma Aldrich) containing 50% by weight of silica with a substantially monodisperse (d=22 nm) particle size distribution.
[0075] A third sol composition was prepared by mixing the following: On the one hand, 36 g of talc / mica particles (Plastorit® Super supplied by Ymeris Performances Additives with a particle size D50 of 3.7 μm), 70 g of an aqueous dispersion of silica containing 50% by weight of silica with a particle size distribution D90 of less than 100 nm (Levasil CT3PL supplied by Nouryon®) and 10 g of acetone on the other hand, 25 g of trimethoxymethylsilane and 1 mL of phosphoric acid as an 85% aqueous solution.
[0076] These two components were then mixed together.
[0077] A fourth sol composition was prepared by mixing the following: On the one hand, 40 g of titanium dioxide particles coated with 4% by weight of alumina (Ti-Pure® R900 supplied by Chemours® (DuPont®) with a median particle size of 410 nm), 70 g of an aqueous dispersion of silica containing 50% by weight of silica with a particle size distribution D90 of less than 100 nm (Levasil CT3PL supplied by Nouryon®) and 15 g of acetone. on the other hand, 60 g of trimethoxymethylsilane and 0.5 mL of phosphoric acid as an 85% aqueous solution.
[0078] These two components were then mixed together.
[0079] A fifth sol composition was prepared by mixing the following: On the one hand, 40 g of titanium dioxide particles coated with 4% by weight of alumina (Ti-Pure® R900 supplied by Chemours® (DuPont®) with a median particle size of 410 nm), 70 g of an aqueous dispersion of silica containing 50% by weight of silica with a particle size distribution D90 of less than 100 nm (Levasil CT3PL supplied by Nouryon®) and 15 g of acetone. - on the other hand, 30 g of trimethoxymethylsilane and 1 mL of 30% ammonia (basic catalyst).
[0080] These two components were then mixed together.
[0081] Table 1 summarizes the content of each element for both the sol composition (wet weight %) and the dielectric layer obtained with this sol composition (dry weight %).
[0082] All compositions, except for the fifth composition, were applied by slot-die coating onto a steel substrate at a wet thickness of about 50 μm. They were dried at a peak metal temperature of 170° C. for 1 minute. They were then annealed at a peak metal temperature of 550° C. for 10 minutes. The fifth sol composition segregated and precipitated due to the presence of the basic catalyst and could not be applied to the steel substrate.
[0083] The results obtained for the first four dielectric coatings obtained from the first four sol compositions are detailed in Table 2.
[0084] The roughness was measured according to standard ISO 1997 (0.5 mm / s, λc=0.8, run=0.5 cm).
[0085] The dielectric performance was evaluated by applying 250V on the dielectric coating with a drop of saturated salt water (approximately 1 cm wide) as contact between the dielectric coating and the top electrode of a gigahommeter and the bottom electrode of the gigahommeter connected to a steel substrate. The resistance should remain above 272 gigahoms for 3 minutes.
[0086] The breakdown voltage was measured by applying a voltage between the upper electrode of the gigahometer, which was in contact with the dielectric layer with a droplet (approximately 1 cm wide) of saturated salt water, and the lower electrode of the gigahometer, which was connected to the steel substrate. The breakdown voltage should be at least 1000V.
[0087] The adhesion of the dielectric coating on the metal substrate was measured by tape testing according to ASTM D3359.
[0088] As is evident from the results, the sol composition according to the invention has a good compromise between roughness, internal stress (assessed through resistance testing), dielectric performance and thermal stability (assessed during annealing). - a sol composition having particles other than titanium dioxide particles with a median diameter of less than 500 nm cannot reach a roughness suitable for electronic applications (sol composition 3); - Sol compositions with precursor levels higher than 30% fail to achieve adequate electrical insulation due to microcracks and porosity (sol composition 4); - Sol compositions with basic catalysts are unstable and segregate.
[0089] [Table 1]
[0090]
Table 2
Claims
1. 1. A sol composition for producing a dielectric layer on a metal substrate, comprising: - 15 to 25% by weight of the sol composition of a precursor comprising a trialkoxysilane, - 20-30% by weight of said sol composition of titanium dioxide particles having a median diameter of less than 500 nm; - 14-30% by weight of said sol composition of silica particles with a particle size distribution D90 of less than 100 nm; - 5-15% by weight of said sol composition of a solvent capable of making said precursor miscible in water; - 0.2 to 0.8% by weight of the sol composition of an acid catalyst, Including, The remainder is water, the sol composition.
2. 2. The sol composition of claim 1, wherein the trialkoxysilane is selected from methyltrialkoxysilane, ethyltrialkoxysilane, and propyltrialkoxysilane.
3. The sol composition according to claim 1 or 2, wherein the precursor is a mixture of at least one tetraalkoxysilane and at least one trialkoxysilane.
4. The sol composition according to any one of claims 1 to 3, wherein the solvent is selected from among alcohols, ketones and mixtures thereof.
5. The titanium dioxide particles are TiO 2 The sol composition according to any one of claims 1 to 4, which is coated with 2 to 6% by weight of alumina on the basis of the weight of the particles.
6. A metal substrate coated on at least a portion of at least one of its surfaces with a dielectric layer of at least 10 μm comprising: - 20-70% by weight of said dielectric layer of titanium dioxide particles having a median diameter of less than 500 nm; - 20-70% by weight of said dielectric layer of silica particles with a particle size distribution D90 of less than 100 nm; - 5 to 10.5% by weight of said dielectric layer of a three-dimensional network of siloxane bonds, - 0.1-2% acid catalyst in said dielectric layer.
7. A method for producing a sol composition, comprising the steps of: providing: o 10 to 25 parts by weight of a precursor comprising a trialkoxysilane; o 20 to 30 parts by weight of titanium dioxide particles having a median diameter of less than 500 nm; o 35 to 55 parts by weight of an aqueous dispersion of silica, the aqueous dispersion comprising 40 to 55% by weight of the aqueous dispersion of silica particles having a particle size distribution D90 of less than 100 nm; o 5 to 15 parts by weight of a solvent capable of making said precursor miscible in water; o 0.2 to 0.8 parts by weight of an acid catalyst, mixing said ingredients.
8. A sol-gel method for producing a dielectric layer on a metal substrate, comprising the steps of: (i) providing said metal substrate and a sol composition comprising: o 15-25% by weight of the sol composition of a precursor comprising a trialkoxysilane; o 20-30% by weight of said sol composition of titanium dioxide particles having a median diameter of less than 500 nm; o 14-30% by weight of the sol composition of silica particles having a particle size distribution D90 of less than 100 nm; o 5-15% by weight of said sol composition of a solvent capable of rendering said precursor miscible in water; 0.2 to 0.8% by weight of the sol composition of an acid catalyst; The remainder is water, (ii) depositing said sol composition onto at least one surface of said metal substrate; - (iii) evaporating said solvent to form a dielectric layer.
9. The method of claim 8, wherein at least 20 μm of the sol composition is deposited.
10. 10. The method according to claim 8 or 9, wherein step (iii) consists of a drying step in which the peak metal temperature of the metal substrate is comprised between 120 and 200°C and the drying time is comprised between 30 seconds and 4 minutes.
11. The method of any one of claims 8 to 10, further comprising step (iv) of annealing the dielectric layer at a peak metal temperature of the metal substrate comprised between 300 and 600°C for a period of between 30 seconds and 4 minutes.
12. A method for manufacturing a solar cell, comprising: (i) providing a metal substrate coated on at least a portion of at least one of its surfaces with a dielectric layer of at least 10 μm comprising: o 20-70% by weight of said dielectric layer of titanium dioxide particles having a median diameter less than 500 nm; o 20-70% by weight of said dielectric layer of silica particles having a particle size distribution D90 of less than 100 nm; o 5-10.5% by weight of said dielectric layer of a three-dimensional network of siloxane bonds; o 0.1-2% acid catalyst in said dielectric layer; (ii) depositing a molybdenum-based rear electrode onto said dielectric layer.
Citation Information
Patent Citations
Coating composition and cured product
JP2001279178A
Liquid curable composition, method of coating, inorganic substrate plate and semiconductor device
JP2008189765A
Hydrophilic primer composition and hydrophilic member
JP2009084454A
Organosiloxane resin composition
JP2012229432A
Aqueous composition, aqueous coating, coating film, and coating product
JP2018193455A